(untitled) (Revista de Ciências Agroveterinárias, 2025)
The objective of this work was to quantify the chemical compounds and the varietal aroma of Sauvignon Blanc wines produced in the high-altitude (above 900 meter) regions of Santa Catarina/Brazil and to compare these with New Zealand Sauvignon Blanc wines, a world reference country for the style of this variety. For the chemical and aromatic description, wines from nine wineries from the altitude regions of 2013 vintage and nine commercial wines from the 2013 vintage from the winegrowing region of Marlborough/New Zealand were selected. Classical analyzes and quantification of phenolic and aromatic compounds of the wines were carried out. In comparison, altitude Sauvignon Blancs have lower residual sugar content, making altitude wines drier than New Zealand wines. Among the 35 compounds identified, 19 contributed individually to the aromas of ’Sauvignon Blanc’, being several esters, higher alcohols and terpenes with similar influence in both regions. However, the varietal thiols 3MH and 3MHA stand out in New Zealand wines, with a great impact on the aroma. The aromatic compounds of high-altitude Sauvignon Blanc wines from Santa Catarina State were consistent between the two evaluated vintages. The compounds that most contributed to the high-altitude Sauvignon Blanc aromas were: isoamyl acetate, ethyl hexanoate, ß-damascenone and ethyl butanoate, related to fruity (apple, pear, banana) and floral aromatic descriptors.